Sistem Pemadam Kebakaran Otomatis Berkonsep Smarthouse - Mikhael Gunawan; Rasional Sitepu; Albert Gunadhi (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2022)
Home fire disasters are still common around us. This problem is a challenge in order to be able to find a solution. One solution to secure a home from a potential fire is to apply smarthome technology. Based on this problem, the idea arose to make an automatic fire extinguisher that can spray water with a water pump when it detects smoke (CO) due to a fire and circulates air in the room with an exhaust fan when an LPG gas cylinder leak is detected in the house so as to prevent a house fire. This tool is planned to be connected to the GSM module so that wherever we are we can find out if there is a fire in our home. This tool is made by utilizing the Smoke Gas Sensor (MQ 2), Temperature Sensor (LM35), Arduino Uno, GSM SIM 900 Module, Relay, Buzer, Exhaust Fan and Water Pump as its main components. Arduino Uno is used as the controller of this machine. The GSM SIM 900 Shield module is used for connection via SMS as a remote notification notification, LM35 as a temperature detector, and MQ 2 as a butane gas detector when there is a leak of LPG gas cylinders and fire smoke (CO) when a fire occurs. This tool can extinguish fires using a water pump from the detection of smoke (CO) and temperatures when more than 500 ppm and 40oC and circulate air using an exhaust fan with additional safety features when there is an LPG gas leak when gas is detected 500 ppm and send it with notification notification via SMS using the GSM SIM 900 module Shield. The measured voltage of the MQ2 sensor when clean air reaches 189.3 mV and the percent error of the LM35 reaches 0.88423%.